Phylogenetic analysis of the genus Hexachlamys (Myrtaceae) based on plastid and nuclear DNA sequences and their taxonomic implications. (26th April 2013) - da Cruz, Fernanda; Turchetto‐Zolet, Andreia C.; Veto, Nicole; Mondin, Cláudio Augusto; Sobral, Marcos; Almerão, Maurício; Margis, Rogério
Abstract : Myrtaceae are one of the most species‐rich families of flowering plants in the Neotropics. They include several complex genera and species; Hexachlamys is one of the complex genera. It has not been recognized as a distinct genus and has been included in Eugenia, based on morphological grounds. Therefore, molecular systematic studies may be useful to understand and to help to solve these relationships. Here, we performed a molecular phylogenetic analysis using plastid and nuclear data in order to check the inclusion of Hexachlamys in Eugenia . Plastid ( accD, rpoB, rpoC1, trnH‐psbA ) and nuclear (ITS2) sequence data were analysed using Bayesian and maximum parsimony methods. The trees constructed using ITS2 and trnH‐psbA were the best able to resolve the relationships between species and genera, revealing the non‐monophyly of Hexachlamys . The molecular phylogenetic analyses were in agreement with previous morphological revisions that have included Hexachlamys in Eugenia . These results reinforce the importance of uniting knowledge and strategies to understand better issues of delimitation of genera and species in groups of plants with taxonomic problems. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 172, 532–543.